PENGEMBANGAN LKPD BERBASIS PROYEK PADA MATA PELAJARAN MATEMATIKA PEMBELAJARAN LUAS BANGUN DATAR SEDERHANA DI KELAS V SD - Anindia Husni Caniago; Nila Lestari (Jurnal Inovasi Penelitian, 2023)
This development research was motivated by the findings of the researchers when conducting observations in class V SD 106450 Cinta Air, that the learning design was still not optimal and the delivery of learning materials was less interesting so that students experienced boredom in learning mathematics. This development research aims to develop a project-based LKPD on the subject of mathematics learning area of ​​simple flat shapes in fifth grade elementary school which is feasible to use. This research is a type of research and development using the ADDIE development model. In this study, the researcher only carried out the ADDIE development model only until the development stage, because the focus of this research was only to develop project-based worksheets on mathematics subjects learning broad simple flat shapes that were suitable for use in the learning process. The instrument used to collect data is a questionnaire or questionnaire given to 3 expert validators, namely material expert validators, language expert validators and learning expert validators. Based on the validation results from the material expert validators, a score of 98 was obtained with the "Very Good" assessment criteria. From the results of the validation of linguists, a score of 92 was obtained with the assessment criteria of "Very Good" and from the results of the validation of learning experts obtained a score of 98 with the assessment criteria of "Very Good". The average score of the three validators is 96. From this score, it can be said that the project-based worksheets on the mathematics subject of simple flat shape learning are "Very Good" to be used in the learning process